The Impact of Leadership Styles and Stress on Employee Turover Intention in Terengganu Hotel Community - Ahmad, Azlinzuraini; Munir Mohd. Salleh, Ahmad; Omar, Khatijah; Abu Bakar, Kamaazura; Abd. Wahab Sha’arani, Karimah (International Journal of Engineering and Technology, 2018)
In the contemporary hotel industry of Terengganu where touristsâ€™ arrivals and competition among firms are encouraging, employees and hotel community are expected to work and upgrade their services which is up to the customersâ€™ expectation. In order to improve customer service, effective leaders could build a culture of trust within their organization and constantly motivating employees to better handle job stress. The employees in hotel industry who need to deal with long working hours, trouble customer, and troubled relationship with supervisor could potentially develop job stress at the workplace. Responding to this issue that requires precise understanding, the objectives of this study are to examine which style of leadership (transformational, transactional and laissez faire) that have significant relationship towards employee turnover intention and to determine stress as a mediator role between leadership and employee turnover intention. A sample of 225 hotel employees from all level of positions of Terengganu hotels was gathered and results of the study showed several significant findings. The most important finding is the significant negative influences of transactional leadership style on employee turnover intention has been found and partial mediation was established when job stress was included. The findings therefore will help to address that the effect of transactional leadership (TL) on employee turnover is increased upon the addition of stress as mediator where subsequently, effective leader could negatively reduce stress and employee turnover intention in hotel industry. Â